Breakthrough infection evokes the nasopharyngeal innate immune responses established by SARS-CoV-2–inactivated vaccine - He, Xiaomeng; Cao, Yingyin; Lu, Yanmei; Qi, Furong; Wang, Haiyan; Liao, Xuejiao; Xu, Gang; Yang, Biao; Ma, Junhua; Li, Dapeng; Tang, Xian; Zhang, Zheng (Frontiers in Immunology, 2023)
Nasopharyngeal immune responses are vital for defense against SARS-CoV-2 infection. Although vaccination via muscle immunization has shown high efficacy in reducing severity and death in COVID-19 infection, breakthrough infection frequently happens due to mutant variants and incompletely-established mucosal immunity, especially in the upper respiratory tract. Here, we performed a single-cell RNA (scRNA) and T cell receptor (TCR) repertories sequencing and delineated a high-resolution transcriptome landscape of nasopharyngeal mucosal immune and epithelial cells in vaccinated persons with breakthrough infection and non-vaccinated persons with natural infection as control. The epithelial cells showed anti-virus gene expression diversity and potentially recruited innate immune cells into the nasopharyngeal mucous of vaccinated patients. Upon infection, where they released significant pro-inflammatory cytokines and chemokines by macrophages and monocytes and expressed antigen-presenting relevant genes by dendritic cells. Such immune responses of nasopharyngeal innate immune cells would facilitate the strengthened expression of cytotoxic genes in virus-specific T cells or B cell differentiation into antibody-secreting cells at the early stage of breakthrough infection through cell interaction between innate and adaptive immune cells. Notably, these alterations of nasopharyngeal immune cells in breakthrough infection depended on the activated NF-kB and NLRP3 signaling rather than type I interferon responses due to the general reduction in ISGs expression. Our findings suggest that vaccination potentially strengthens innate immune barriers and virus-specific memory immune cell responses, which could be quickly activated to defend against variant breakthrough infection and maintain nasopharyngeal epithelial cell integrity. Thus, this study highlights the necessity of a boost via nasal mucous post-intramuscular immunization.